2007
DOI: 10.1071/rd07015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cell cycle and extracellular matrix gene expression during placental development in deer mouse (Peromyscus) hybrids

Abstract: Abstract.Crosses between two species of the rodent genus Peromyscus produce defects in both growth and development. The defects are pronounced in the hybrid placentas. Peromyscuys maniculatus (strain BW) females mated to P. polionotus (strain PO) males produce placentas half the size of the parental species, as well as growth-retarded embryos. In contrast, PO females mated to BW males result in defective conceptuses that display embryonic and placental overgrowth. These 'parent-of-origin'-dependent phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 76 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…Moreover, the walls of the maternal blood sinuses within the female PO 3 male BW labyrinth typically appear thinner and often compromised. These defects are consistent with the previously documented reduction in female PO 3 male BW placental collagen expression as well as similar hemorrhaging in the associated embryos [11,20].…”
Section: Duselis and Vranasupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, the walls of the maternal blood sinuses within the female PO 3 male BW labyrinth typically appear thinner and often compromised. These defects are consistent with the previously documented reduction in female PO 3 male BW placental collagen expression as well as similar hemorrhaging in the associated embryos [11,20].…”
Section: Duselis and Vranasupporting
confidence: 91%
“…This suggests that a possible underlying cause of embryonic death may be failure of maternal-fetal nutrient transfer due to blood vessel instability in the labyrinth. Moreover, our previous research suggested a deficiency of some ECM-related proteins in female PO 3 male BW placentas [20]. …”
Section: Female Po 3 Male Bw Hybrid Placental Hemorrhagingmentioning
confidence: 90%
See 3 more Smart Citations